STRATEGI INDONESIA MENINGKATKAN EKSPOR PRODUK HALAL KE ORGANISASI KERJASAMA ISLAM TAHUN 2017-2019 - Kevin Alif Fathurrahmad; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study intends to analyze Indonesia’s strategy to increase exports of halal trading activities of halal product in Organisation of Islamic Cooperation market. The existence of human resource factors and the opportunity for Indonesia to market halal-labeled product in global market by carrying out the export of halal products. The Indonesian Government carries out a strategy to increase halal products marketed in international market especially OIC.In this study, the authors used library research and qualitative research methods. The analysis in this study uses the level of analysis of nation state, the concept of national interest, using the theory of international trade and competitive advantage. The use of this theory is because the research discusses Indonesia’s economic trade cooperation with the uniqueness of goods and focus of the target market. The perspective in this study uses the perpective of mercantilism.The result of this research is export of Indonesian halal products is cooperative activity in the economic sector and is expected to provide benefits for Indonesia through various schemes implemented. In general, the export of halal products has a broad scope with the aim of strengthening economic with Organisation of Islamic Cooperation.Keyword(s) : Strategy, Export, Halal Product, Organisation of Islamic Cooperation.